2022
DOI: 10.1002/srin.202100785
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deep Cryogenic Treatment on Microstructural Evolution and Transformation Kinetics Simulation by Finite Element Method of Low‐Carbon High‐Alloy Martensitic‐Bearing Steel

Abstract: Nowadays, deep cryogenic treatment (DCT) is taken as a promising technique for improving the performance of steel. This article is focused on the influence of different heat treatment processes involving DCT on the microstructural evolution of a high Cr-Co-Mo high-temperature-bearing steel. Moreover, a multiphysical field coupling numerical model is built to investigate the martensitic transformation kinetics during DCT. The results show that DCT significantly improves the hardness and promotes the transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…For instance, it was found that CT at −196 • C (following sequence A) reduced the RA from 26 vol.% to one tenth of this value in the case of the steel with 0.15% C, 14% Cr, 13% Co, 2.4% Ni, and 4.8% Mo [69]. Similar results were also obtained through cryogenic treatment of X30CrMoN15 1 steel [71], an experimental steel with 0.17% C, 15% Cr, 11% Co, 3.3% Mo, 2.5% Ni, and 2% W [321], or AISI 440C steel [16], both treated via sequence A. Repeated CT cycles may further decrease the RA, but only to a very limited extent [17].…”
Section: Martensitic Stainless Steelssupporting
confidence: 69%
See 2 more Smart Citations
“…For instance, it was found that CT at −196 • C (following sequence A) reduced the RA from 26 vol.% to one tenth of this value in the case of the steel with 0.15% C, 14% Cr, 13% Co, 2.4% Ni, and 4.8% Mo [69]. Similar results were also obtained through cryogenic treatment of X30CrMoN15 1 steel [71], an experimental steel with 0.17% C, 15% Cr, 11% Co, 3.3% Mo, 2.5% Ni, and 2% W [321], or AISI 440C steel [16], both treated via sequence A. Repeated CT cycles may further decrease the RA, but only to a very limited extent [17].…”
Section: Martensitic Stainless Steelssupporting
confidence: 69%
“…The hardness of 0.15% C-14% Cr-13% Co-4.8% Mo-2.4% Ni steel austenitised at 1020 • C increased by 7 HRC by subjecting it to CT at −196 • C for 2 or 10 h (following sequence A) [69,70]. Very consistent results were obtained by cryogenic treatments of 0.17% C, 15% Cr, 11% Co, 3.3% Mo, 2.5% Ni, and 2% W steel at −196 • C for 20 h [321]. Cryogenic treatment at −196 • C for 10 h increased the hardness by 12 HRC after hardening from 1050 • C, indicating that the given CT effectively reduced the RA [69].…”
Section: Martensitic Stainless Steelsmentioning
confidence: 53%
See 1 more Smart Citation